Correlation Between the Degree of Midline Shift in Computed Tomography Scan of Brain and Level of Consciousness of the Patients with Acute Spontaneous Intracerebral Haemorrhage - Islam, Md Quamrul; Rahman, Arifur; Bahar, Hijbul; Hossain, Mousumi; Rabbi, Akand Fazle; Asaduzzaman, Md (Sir Salimullah Medical College Journal, 2023)
Background: Intracerebral hemorrhage (ICH) is the second most common cause of stroke, following ischemic stroke, but accounts for a disproportionate amount of cerebrovascular mortality and morbidity. The extent of midline shift, observed on computed tomography (CT) scans, has been recognized as an important radiological finding associated with the severity of ICH. Objective: To evaluate correlation between the degree of midline shift in computed tomography scan of brain and level of consciousness of the patients with acute spontaneous intracerebral haemorrhage. Material and method: This cross-sectional study was carried out in 100 patients, out of this 50 had spontaneous intracerebral hemorrhage with mass effect and 50 had spontaneous intracerebral hemorrhage without mass effect taken as the control group, the age range from 30-75 years. These patients were purposively collected from the Department of Radiology and Imaging in collaboration with Department of Medicine, Neuromedicine and Neurosurgery of Dhaka Medical College Hospital, Dhaka. All the patients were evaluated by CT findings. On admission Glasgow Coma Scale (GCS) score were recorded from participant’s treatment sheet and reviewed by the senior Neurologist after taking permission of the authority. Results: This study shows there is significant inversely correlation of the GSC score with degree of midline shift measure using septum pellucidum shift (P<0.05). The GCS score of <10 mm of septum pellucidum shift compared to greater than 10 mm of septum pellucidum shift is significantly different (P<0.05). The GCS score of SICH with mass effect compared to the GCS score of SICH without mass effect is significantly different (P<0.05). Conclusion: Radiologist should carefully and elaborately interpret the spontaneous intracerebral hemorrhage with midline shift at CT-scan brain and help clinicians to evaluate the level of consciousness which is significant predictor of outcome of our valuable patients. Sir Salimullah Med Coll J 2023; 31: 94-99